Calculations in molecular biology and biotechnology : a guide to mathematics in the laboratory - Stephenson, Frank H. (Academic Press, 2003)
Calculations in Molecular Biology and Biotechnology: A Guide to Mathematics in the Laboratory is the first comprehensive guide devoted exclusively to calculations encountered in the genetic engineering laboratory. Mathematics, as a vital component of the successful design and interpretation of basic research, is used daily in laboratory work. This guide, written for students, technicians, and scientists, provides example calculations for the most frequently confronted problems encountered in gene discovery and analysis. The text and sample calculations are written in an easy-to-follow format. It is the perfect laboratory companion for anyone working in DNA manipulation and analysis. *A comprehensive guide to calculations for a wide variety of problems encountered in the basic research laboratory. * Example calculations are worked through from start to finish in easy-to-follow steps * Key chapters devoted to calculations encountered when working with bacteria, phage, PCR, radioisotopes, recombinant DNA, centrifugation, oligonucleotides, protein, and forensic science. *Written for students and laboratory technicians but a useful reference for the more experienced researcher. *A valuable teaching resource.